2004
DOI: 10.1088/1126-6708/2004/11/075
|View full text |Cite
|
Sign up to set email alerts
|

Supersymmetric Embedding of the Quantum Hall Matrix Model

Abstract: We develop a supersymmetric extension of the Susskind-Polychronakos matrix theory for the quantum Hall fluids. This is done by considering a system combining two sets of different particles and using both a component field method as well as world line superfields. Our construction yields a class of models for fractional quantum Hall systems with two phases U and D involving, respectively N 1 bosons and N 2 fermions. We build the corresponding supersymmetric matrix action, derive and solve the supersymmetric ge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Also, it has been shown that, in the supermatrix model, fluctuations on a fuzzy supersphere yield supersymmetric NC field theories [27]. Besides, some interesting relations between NAC geometry, Landau problems, and QH systems are reported [28][29][30][31]. Specifically, on a fuzzy supersphere, a supersymmetric extension of QH liquid was explicitly constructed in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Also, it has been shown that, in the supermatrix model, fluctuations on a fuzzy supersphere yield supersymmetric NC field theories [27]. Besides, some interesting relations between NAC geometry, Landau problems, and QH systems are reported [28][29][30][31]. Specifically, on a fuzzy supersphere, a supersymmetric extension of QH liquid was explicitly constructed in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The conformal mechanical models are typically characterized by the inversesquare potential 5 . Inverse-square potential in quantum mechanics is a jewellery box in theoretical physics and mathematics containing black hole physics [65,66,67,68,69,70,71,72,73,74,75,76,77], AdS 2 /CFT 1 correspondence [78,79,80,81,82,83,84,85,86,87], QCD [88,89], quantum Hall effect [90,91], Tomonaga-Luttinger liquid [92], string theory [93,94,95,96,97,98], spin chains [99,100,101,102,103,104,105,106], Efimov effect [107,108,109,110], mesoscopic physics…”
Section: Historical Backgroundmentioning
confidence: 99%
“…with 10) and ∂ 0 = ξ ∂ ∂ξ = ∂ ∂ ln ξ and where d 3 v is the conifold holomorphic volume measure given by,…”
Section: Classical B Rr -D String Couplingmentioning
confidence: 99%